Allergic Aspects of IgG4-Related Disease: Implications for Pathogenesis and Therapy - Michailidou, Despina; Schwartz, Daniella Muallem; Mustelin, Tomas; Hughes, Grant C. (Frontiers in Immunology, 2021)
IgG4-related disease (IgG4-RD) is a rare systemic fibroinflammatory disease frequently associated with allergy. The pathogenesis of IgG4-RD is poorly understood, and effective therapies are limited. However, IgG4-RD appears to involve some of the same pathogenic mechanisms observed in allergic disease, such as T helper 2 (Th2) and regulatory T cell (Treg) activation, IgG4 and IgE hypersecretion, and blood/tissue eosinophilia. In addition, IgG4-RD tissue fibrosis appears to involve activation of basophils and mast cells and their release of alarmins and cytokines. In this article, we review allergy-like features of IgG4-RD and highlight targeted therapies for allergy that have potential in treating patients with IgG4-RD.